CHRNA4 was associated with prepulse inhibition of schizophrenia in Chinese: a pilot study. Issue 2 (3rd March 2016) - Shi, Jing; Wang, Zhiren; Tan, Yunlong; Fan, Hongzhen; An, Huimei; Zuo, Lingjun; Yang, Fude; Tan, Shuping; Li, Jia; Zhang, Xiangyang; Zhou, Dongfeng; Luo, Xingguang
ABSTRACT: Introduction : Prepulse inhibition (PPI) of the auditory startle reflex, as an operational measurement used to evaluate the function of brain sensorimotor gating, appears to be a sensitive potential endophenotype for schizophrenia. CHRNA4 is highly expressed in the central nervous system and has been demonstrated to be significantly associated with schizophrenia by previous studies. The purpose of the current study was to evaluate the effect of CHRNA4 on PPI and acoustic startle parameters in schizophrenia. Methods : 77 patients with schizophrenia and 62 controls were administered the test PPI, and 3 single nucleotide polymorphisms (SNPs) (rs3746372, rs1044396, and rs3787140) of CHRNA4 were genotyped in these subjects. Results : Patients with schizophrenia showed significantly lower levels of PPI at the 120 ms prepulse intervals and longer peak latency than controls, and the GG genotype of rs3746372 and the TT genotype of rs1044396 were associated with decreased PPI levels in schizophrenia but not in controls. Conclusion : PPI may be influenced by the polymorphisms of the CHRNA4 in schizophrenia and it may be a potential endophenotype of schizophrenia. An independent replication would greatly increase the value of this study.